(untitled) (SCIÉNDO INGENIUM, 2024)
This study analyzes the technical feasibility of using mining tailings from Nexa Resources as raw material for cement production, promoting a circular economy approach. The methodology includes conditioning the tailings through flotation, thermal treatment for clinker production, and subsequent grinding. A flotation circuit was optimized by selecting specific reagents, such as carbonate collectors and silica depressants, which increased the carbonate content and reduced silica and pyrite levels. This ensured the appropriate proportions of Ca, Si, Al, and Fe required to maintain clinker quality. At a pilot scale, more than 5 tons of clinker were produced, resulting in cement that meets the standards of Portland cement. This cement was successfully tested in shotcrete and paste fill applications, meeting the requirements for compressive strength and energy absorption. The results confirm the technical feasibility of producing high-quality cement from mining tailings, representing a significant step toward sustainability in the mining industry by providing solutions for waste management and reducing the environmental footprint.